Comparison of breastfeeding knowledge and attitudes of selected adolescent males and females from rural and metropolitan secondary schools - Juliff, Dianne Therese (Curtin University, 2005)
Research has indicated that adolescents hold both negative and positive attitudes and have common misconceptions about breastfeeding that appear to result from their limited knowledge and reduced exposure to breastfeeding. The purpose of this study was to determine the knowledge and attitudes toward breastfeeding of adolescent male and female secondary school students. The study also sought to elicit information on factors that may influence the decision regarding future infant feeding methods. Self-efficacy theory was the theoretical framework to guide the study. This quantitative descriptive study, using a cross-sectional design, involved consenting secondary school students' completing a self-report questionnaire. The study employed purposive sampling and included 1845 males and females in both year-nine and year-12 at designated metropolitan and rural secondary schools in 2001. Analyses of the data were performed using the Statistical Package for Social Science (version 10.7). Statistical procedures involved chi-square analysis, Student's independent t-test and univariate analysis of variance. Spearman's rank order correlation coefficient was used to describe the relationship between the secondary school student respondents' knowledge of and their attitudes toward breastfeeding. The study results indicate that overall Western Australian adolescent secondary school students have less than ideal knowledge of breastfeeding which is consistent with findings from other studies. Higher breastfeeding knowledge scores were reported in year-12 for both male and female students. For both year groups, female students had higher breastfeeding knowledge scores than male students. With regards to attitudes toward breastfeeding, students had a tendency for neutral responses to attitude questions.However, overall and for both year groups, female students were found to be more positive towards breastfeeding than male students. The comparison of rural to metropolitan students found that metropolitan students had higher breastfeeding knowledge and were more positive towards breastfeeding than rural students. The metropolitan students were also more inclined to consider breastfeeding future children than rural students. Consideration of breastfeeding future children was similar for both male and female students. Comparison of the combination of gender, year and site revealed higher breastfeeding knowledge and more positive attitudes to breastfeeding in both rural and metropolitan female year-12 respondents. Sources of efficacy information, particularly persuasion/education, were more prominent in female secondary school respondents than male secondary school respondents when considering factors influencing adolescent attitudes toward breastfeeding. The adolescent's acceptance of gender identity could be argued as a reason for the more positive breastfeeding attitudes in female respondents. Students who were breastfed or exposed to breastfeeding either through role models (ie mothers), reading about breastfeeding, media or family influence had greater knowledge and were more positive towards breastfeeding. This study suggests that breastfeeding and lactation information needs to be addressed in the early years of development in order to increase breastfeeding knowledge and promote positive attitudes. Information pertinent to the health benefits of breastfeeding needs to be included in health and nutrition education and addressed through targeted education programs.Education and health promotion activities could be guided using the four sources of efficacy information in relation to the benefits of breastfeeding. Opportunities for the role modelling of positive breastfeeding attitudes, and consistent support from the school-based health professionals may assist to reduce the adolescent student's unmet informational needs in relation to breastfeeding. A recommendation from this study is the provision of lactation and breastfeeding education for community-based high school nurses as these health professionals are a key element in health education and health promotion in the school setting.